DOES FILIAL DISCREPANCY AFFECT DEPRESSIVE SYMPTOMS AFTER TWO YEARS: A LONGITUDINAL STUDY. (16th November 2018) - Chau, W; Dong, X; Kong, D; Li, M; Bergren, S
Abstract: For centuries, in traditional Chinese culture, filial piety are considered as the highest of all virtues. A previous cross-sectional study reported a significant relationship between filial discrepancy and psychological well-being among U.S. Chinese older adults. However, less is known regarding the longitudinal relationship between filial discrepancy and psychological wellbeing over time. This study aimed to examine the relationship between filial discrepancy and depressive symptoms using two-wave data. Depressive symptoms were measured by nine-item Patient Health Questionnaire. Change of depressive symptoms was calculated by wave 2 minus wave 1 scores. Negative binomial and linear regressions were performed. Filial expectation was associated with increase in depressive symptoms during two years (b = .03, SE = .01). Larger filial expectation than receipt was associated with larger increase in depressive symptoms (b = .04, SE = .01) and higher level of depressive symptoms after two years (RR, 1.02 [1.00, 1.03]). The result showed a positive association between filial discrepancy and depressive symptoms; intensified depressive symptoms that prolonged in the two years of research. Our findings suggested that early identification and intervention for Chinese older adults with filial discrepancy are necessary to help them maintain optimal psychological wellbeing in later life. Depressive symptoms have a wide range of intensity, can lead to a serious condition that requires immediate medical treatment which also interferes with daily life. Due to the cultural differences, findings suggested that Chinese older adults mainly have high filial expectations and low receipt; recognizing depressive symptoms may require extra attention.